Bridging N-doped graphene and carbon rich C3N4 layers for photo-promoted multi-functional electrocatalysts. (10th September 2019) - Yang, Yimei; Hu, Baoshan; Zhao, Wenbin; Yang, Qian; Yang, Feng; Ren, Juncong; Li, Xiaogang; Jin, Yan; Fang, Liang; Pan, Qingjiang
Abstract: Distinctive electronegativity and similar atomic radius for elements of C and N afford their allotropic substances composed of these two elements with excellent photo- and electro-chemical performance for energy conversion. To explore the synergetic roles of allotropic substances, carbon-rich C3 N4 (CCN) is in - situ hydrothermally synthesized with the N-doped graphene (NG) grown by chemical vapor deposition (CVD) as the template to prepare the N-doped graphene/carbon-rich C3 N4 composite. Compared to the N-doped graphene and carbon-rich C3 N4, N-doped graphene/carbon-rich C3 N4 composite exhibits the remarkable enhancement of catalytic activities toward hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). Particularly, visible light irradiation can significantly improve the catalytic performance of N-doped graphene/carbon-rich C3 N4 toward the above three reactions. Further results confirm that N-doped graphene/carbon-rich C3 N4 exhibits the improved electrochemically active surface area (ECSA), light-harvesting ability, effective separation of electron-hole pairs, and interfacial charge transfer as compared to the N-doped graphene and carbon-rich C3 N4 which should be originated from the efficient bridging between N-doped graphene and carbon-rich C3 N4 layers. Our elucidation facilitates to pave their promising applications in microelectronic devices, wearable devices, photoelectrochemical batteries, sensors and other fields. Graphical abstract: Image 1